HBV Biomarkers and Their Role in Guiding Treatment Decisions - Mak, Lung-Yi; Boettler, Tobias; Gill, Upkar S. (Seminars in Liver Disease, 2024)
Over 300 million individuals worldwide are chronically infected with hepatitis B virus and at risk for progressive liver disease. Due to the lack of a therapy that reliably achieves viral elimination and the variability of liver disease progression, treatment decisions are guided by the degree of liver disease and viral biomarkers as the viral life-cycle is well characterized and largely conserved between individuals. In contrast, the immunological landscape is much more heterogeneous and diverse and the measurement of its components is less well standardized. Due to the lack of a universal and easily measurable set of biomarkers, clinical practice guidelines remain controversial, aiming for a balance between simplifying treatment decisions by reducing biomarker requirements and using all available biomarkers to avoid overtreatment of patients with low risk for disease progression. While approved therapies such as nucleos(t)ide analogs improve patient outcomes, the inability to achieve a complete cure highlights the need for novel therapies. Since no treatment candidate has demonstrated universal efficacy, biomarkers will remain important for treatment stratification. Here, we summarize the current knowledge on virological and immunological biomarkers with a specific focus on how they might be beneficial in guiding treatment decisions in chronic hepatitis B.
Keywords: functional cure; finite treatment; risk stratification; treatment response; host–viral interaction